THE MEANING OF BEAUTY AS INSPIRATION AND MOVEMENT OF CHANGE IN THE “BEAUTY MOVES YOU” VERSION OF WARDAH ADVERTISEMENT - Ahmad Yazid Lubis; Lina Maurissa; Ocvita Ardhiani (Journal of Digital Media Communication, 2022)
This study aims to explore the meaning of beauty as an inspiration and movement of change for Indonesian women in the Wardah advertisement version of "Beauty Moves You". This study uses a qualitative descriptive approach, while the analytical technique used is Roland Barthes ' semiotic analysis which involves denotation, connotation and myth signs. The stages of analysis that will be used by researchers are collecting units of analysis from the object of research in the form of images, text on images, audio (dialogue) in several scenes main advertisement, the researcher describes the signs and meanings from each unit of analysis. Based on the results of the analysis of the meaning of denotation, connotation, and myth in the six main scenes and in the whole advertisement in general, several signifieds and signifiers were found to interpret the beauty standards of Indonesian women, namely clothing, physical beauty, and beauty as an inspiration and movement of change. Beauty picture as inspiration and mover change in advertisement it also invites modern girl for change pattern think and awaken the women that beauty that already there is in each woman. Women are encouraged to have the courage to appear confident, to love themselves more, to have the courage to develop self-competence to inspire and drive change for their surroundings. Advertisement this clear have draft different from most advertisement cosmetics in general, Wardah give the other side of beauty for encourage trust self, intelligence, optimism and ability every woman for inspire many people through their respective roles. Advertisement Wardah the version of “Beauty Moves You” interprets girls also have role as actor mover change with the expected beauty could give impact as well as positive benefits for environment fellow.